Illegal Journey: The Indonesian Undocumented Migrant Workers to Malaysia - Ridwan Wahyudi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2017)
The objective of this study is threefold. First, it uses fieldwork to explore the illegal journey of the Indonesian undocumented migrant workers, including all processes and interactions. Secondly, it identifies the substantive factors behind illegal influx into Malaysia. Thirdly, it draws out the implications from the illegal journey undertaken by them to Malaysia. This qualitative study applies the grounded theory approach. The result of this study shows that social capital within their network expands through various channels, particularly friendship, brotherhood, neighborhood, community and ethnic grouping. It also permeates strongly beyond government authority and regulation. They have constructed social classes among themselves. However, they have also been less able to get the social access because the absence of official documents deprives their human rights, and they are also blamed for social ills. Therefore, the regulation for both countries must recognize the rights, improvement governance, strengthen the integrity and curb corruption.